A cross-sectional study of road traffic accident victims at a tertiary care teaching hospital at Gwalior city in Madhya Pradesh of Central India - Khare, Gaurav; Tiwari, Ranjana; Aurfat Kausar Nazir,; Shukla, Durgesh; Verma, Rani; Achale, Sapna (Asian Journal of Medical Sciences, 2023)
Background: Road crash deaths in India, which were the highest in the world, are a burden on its demographic dividend and have a tangible impact on poverty. Aims and Objectives: The present study was conducted to investigate the sociodemographic characteristics, type of vehicle, types of road, primary treatment, and safety measures adopted by the victims of road traffic accidents (RTA). Materials and Methods: The present cross-sectional study was conducted at Trauma Center, Madhav Dispensary, J.A. Group of Hospitals Gwalior, M.P. on 528 Victims of RTA between the period of January 01, 2020, and June 30, 2021. The descriptive statistical measures such as mean, standard deviation, frequency, and percentage were used. The data analysis was done in Microsoft Excel Software. Results: In the present study, a total of 528 RTA victims were enquired. Their average age was 33.02±13.31 years, with 81.8% were male and 18.2% were female. Most of the victims (67.80%) were on two-wheeler vehicles. About half of the victims were found to have Head on Collision during accidents. The accidents mostly occurred in the time period from 9.00 am to 9.00 pm. It was observed that 65.90% RTA victims had soft-tissue injury and bony injury. Conclusion: It was vital to obtain valid information of the real importance of RTA along with the preventive action concerning RTAs. It was recommended to provide the basic treatment to victims related with RTA at Primary Care Center of the nearest accident place.